Peri-procedural Trans-esophageal Echocardiographic Sizing of the Native Left Ventricular Outflow Tract During Edwards INTUITY Valve Implantation - Lim, Kevin; Ho, Yan Kit; Chow, Simon Chi Ying; Fujikawa, Takuya; Lee, Alex Pui-Wai; Wong, Randolph Hung Leung (Frontiers in Cardiovascular Medicine, 2021)
Background: The Edwards INTUITY rapid deployment valve was anchored on the left ventricular outflow tract (LVOT) by radial force akin to transcatheter balloon-expandable valves. This design feature facilitates minimally invasive and complex procedures but comes at the price of compressing the atrioventricular conduction bundle and potential requirement for pacemaker implantation. Methods: A retrospective observational study was conducted on 30 consecutive patients who received the INTUITY valve at our institution from August 2018 to January 2021. Demographical, clinical, and echocardiographic parameters were collected for 90 days post-operatively. The diameter of the native LVOT at the landing site of the sub-annular stent was retrospectively measured using archived trans-esophageal echocardiographic images. A line was drawn from the inner edge of the septal endocardium to the inner edge of the anterior mitral leaflet in mid-systole, parallel to the aortic annulus, 6–8 mm apical to the aortic annulus depending on the valve size and the corresponding stent length. Risk factors associated with new onset conduction disturbances, defined as the occurrence of bundle branch block or complete heart block, were analyzed. Results: Operative mortality was 3.3%. Pre-operatively, permanent pacemakers were required for two patients who were excluded from the subsequent analysis. New onset conduction disturbances occurred in four of the remaining 28 patients (14.3%). This included two incidences of persistent left bundle branch block and two incidences of permanent pacemaker implantation due to complete heart block. Univariate analysis identified over-sizing of the native LVOT by 5 mm or more as a significant risk factor associated with conduction disturbance. Conclusion: During INTUITY vale implantation, in addition to the aortic annulus, the landing site of the sub-annular stent within the native LVOT should also be sized pre-bypass. Over-sizing the native LVOT by 5 mm or more was associated with an increased risk of new onset conduction disturbances and should be avoided.